The Influence of Environmental Accounting, Environmental Performance, and CSR on the Financial Performance of Manufacturing Companies Listed on the Indonesia Stock Exchange from 2019-2022 - Anthoni, Dhea Fitri; Cerya, Efni (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the influence of Environmental Accounting, Environmental Performance, and Corporate Social Responsibility (CSR) on Financial Performance. This study comprises three independent variables: Environmental Accounting is measured using environmental cost disclosure, Environmental Performance is measured using the PROPER framework, and Corporate Social Responsibility (CSR) is measured using the GRI Standard Index. The dependent variable, Financial Performance, is proxied by Return on Assets (ROA). The sample in this study comprises 221 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022; however, only 15 companies met the sample criteria. The sample selection method used was Purposive Sampling. Based on this, a total of 60 data points were obtained from the 15 companies, multiplied by four periods. The data used in this study are secondary data sourced from the financial reports of manufacturing companies published on the Indonesia Stock Exchange. Data analysis was conducted using multiple regression analysis, with SPSS 29 used for data processing. The results of the study indicate that environmental accounting and CSR have a significant negative impact on financial performance. Meanwhile, environmental performance has no significant impact on financial performance. Overall, environmental accounting, environmental performance, and Corporate Social Responsibility (CSR) simultaneously influence financial performance. These findings suggest that companies should carefully assess how they manage and communicate their environmental cost disclosures and CSR initiatives, as they may not always be perceived positively by stakeholders. Enhancing transparency, strategic alignment, and stakeholder engagement in sustainability practices could improve the financial outcomes.